Imaging the lithospheric structure beneath the Indian continent. Issue 10 (30th October 2016) - Maurya, S.; Montagner, J.‐P.; Kumar, M. Ravi; Stutzmann, E.; Kiselev, S.; Burgos, G.; Rao, N. Purnachandra; Srinagesh, D.
Abstract: We present a high‐resolution 3‐D lithospheric model of the Indian plate region down to 300 km depth, obtained by inverting a new massive database of surface wave observations, using classical tomographic methods. Data are collected from more than 550 seismic broadband stations spanning the Indian subcontinent and surrounding regions. The Rayleigh wave dispersion measurements along 14, 000 paths are made in a broad frequency range (16–250 s). Our regionalized surface wave (group and phase) dispersion data are inverted at depth in two steps: first an isotropic inversion and next an anisotropic inversion of the phase velocity including the SV wave velocity and azimuthal anisotropy, based on the perturbation theory. We are able to recover most of the known geological structures in the region, such as the slow velocities associated with the thick crust in the Himalaya and Tibetan plateau and the fast velocities associated with the Indian Precambrian shield. Our estimates of the depth to the Lithosphere‐Asthenosphere boundary (LAB) derived from seismic velocity Vsv reductions at depth reveal large variations (120–250 km) beneath the different cratonic blocks. The lithospheric thickness is 120 km in the eastern Dharwar, 160 km in the western Dharwar, 140–200 km in Bastar, and 160–200 km in the Singhbhum Craton. The thickest (200–250 km) cratonic roots are present beneath central India. A low velocity layer associated with the midlithospheric discontinuity is present when the root of the lithosphere is deep. Key Points: New massive surface wave data set assembled for this work First high‐resolution 3‐D shear wave velocity model for the Indian continent Our 3‐D model explains most of the geological features and different cratonic blocks